Improving the Early Assessment of Child Neglect Signs-A New Technique for Professionals - Giovanni Giulio Valtolina; Concetta Polizzi; Giovanna Perricone (MDPI AG, 2023)
This paper grants some considerations on a critical phenomenon for child health: child neglect. It is an omission-type form of childhood maltreatment, which is widespread but very hard to intercept. For the assessment of child neglect, the Italian Society of Pediatric Psychology (S.I.P.Ped.) has developed and validated a specific assessment technique (the C.N.A. technique). It is supposed to be for parents of children between 3 and 9 years old. It is based on a paradigm that identifies the dysregulation of parental competence as the cause of neglect. It can occur in hypo- or hyperactivation of three fundamental factors (recognition, stimulation, and care). The child neglect assessment technique (C.N.A.) differs from the retrospective tools available in the literature since it allows for interception of the "signs" of possible child neglect when negligence occurs.